ANALYSIS OF FACTORS AFFECTING SME PERFORMANCE THROUGH EMPLOYEE JOB SATISFACTION - Suparjo, Suparjo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research was undertaken to understand and analyze the impact of leadership style and skill on lecturers' motivation and output. This study was chosen to address the issues and trends relating to job satisfaction. Although several components are involved, the authors have a preliminary hunch that the skill factor and leadership style may impact lecturer motivation and performance, affecting and boosting job satisfaction and lecturer performance. A questionnaire is the tool of choice for gathering data for the study. There were 30 questionnaires distributed to the respondents. Descriptive analysis and questionnaire feasibility tests were employed as data analysis approaches. These tests were previously validated using tests for reliability, validity, multicollinearity, coefficient of determination, and Path Analysis (Path Analysis) with smart-pls software. According to the study's findings, The model depicts SME performance, work environment, job happiness, communication style, and leadership style. The model demonstrates that while leadership style does not affect either job happiness or SME performance, communication and the workplace environment have a significant positive impact. A good work environment and job satisfaction can improve SMEs' performance well. The indirect model shows that what influences enhancing the performance of SMEs through reasonable job satisfaction is good communication and a good and optimal work environment.